Social Entrepreneurship and its Hybridity in Determining Resource Challenges and Chances - Starnawska , Marzena (Studia Oeconomica Posnaniensia, 2016)
In this conceptual paper the author aims to grasp what are the particular challenges and opportunities in social entrepreneurship in terms of resource access and mobilization, considering the hybrid nature of social enterprise. To this end the author points to the nature of hybridity and discusses what advantages and disadvantages are inherent in financial, human and physical resource access for social enterprises as hybrid organizations. This discussion is enriched by analysing intangible resources such as relational, institutional and cultural that distinguish social entrepreneurship as an institutional type of entrepreneurship as well.